2014
DOI: 10.3233/nre-131020
|View full text |Cite
|
Sign up to set email alerts
|

Aerobic exercises enhance cognitive functions and brain derived neurotrophic factor in ischemic stroke patients

Abstract: BACKGROUND: Stroke is a leading cause of functional impairments. High percentage of these patients will experience some degree of cognitive affection, ranging from mild cognitive impairment to dementia. OBJECTIVE: Demonstrate the role of aerobic exercises enhancing cognitive functions and its effect on Brain Derived Neurotrophic factor (BDNF) in post-ischemic stroke patients in the territory of anterior circulation. SUBJECTS AND METHODS:We included thirty Egyptian ischemic stroke patients in the territory of a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 90 publications
(93 citation statements)
references
References 21 publications
1
89
0
3
Order By: Relevance
“…While these neuroimaging data do not necessarily correlate with behavioral changes, these results can provide insight into potential mechanisms underlying the effects of training on function. In animal models, treadmill exercise was associated with increased cortical levels of brain-derived neurotrophic factor (BDNF) (37), and preliminary work in humans has demonstrated that exerciserelated improvements in post-stroke cognition are associated with increased serum BDNF levels (38).…”
Section: Discussionmentioning
confidence: 99%
“…While these neuroimaging data do not necessarily correlate with behavioral changes, these results can provide insight into potential mechanisms underlying the effects of training on function. In animal models, treadmill exercise was associated with increased cortical levels of brain-derived neurotrophic factor (BDNF) (37), and preliminary work in humans has demonstrated that exerciserelated improvements in post-stroke cognition are associated with increased serum BDNF levels (38).…”
Section: Discussionmentioning
confidence: 99%
“…This study sought to capitalize on the beneficial effects of aerobic exercise on language 42 and cognitive function in previous studies involving older adults and individuals poststroke. 3,4,17,43 Interpretation of the results requires the consideration of crucial factors that include mechanisms of effect, timing, intensity, and individual factors.…”
Section: Considerations Related To Exercise Interventionmentioning
confidence: 99%
“…2 Importantly, reviews suggest that cognitive abilities after stroke may also improve with exercise. 3,4 Indeed, recent studies have demonstrated a positive effect of exercise on executive function, 5,6 speed of information processing, 7 memory, 5,8 and even language. 8 These results are promising and highlight the need for more research investigating the use of exercise for improving cognitive function in individuals with chronic history.…”
Section: Introductionmentioning
confidence: 99%
“…Voluntary wheel‐running has been shown to increase BDNF mRNA production in the hippocampus and neocortex of rats (Neeper et al ., ), suggesting that exercise induces BDNF production via upregulation of BDNF gene transcription. While in vivo measurement of central BDNF in humans is not feasible, numerous studies have measured peripheral BDNF concentrations after exercise, with some studies finding increases (Griffin et al ., ; Cho et al ., ; Coelho et al ., ; Schmolesky et al ., ; El‐Tamawy et al ., ; Salehi et al ., ; Jeon & Ha, ) and others reporting no significant changes in BDNF after exercise (Correia et al ., ; Stroehle et al ., ; Bos et al ., ; McDonnell et al ., ; Gapin et al ., ; Schuch et al ., ). Thus, evidence regarding the effects of acute exercise on peripheral BDNF is inconsistent.…”
Section: Introductionmentioning
confidence: 98%